Ny-Ålesund-oriented organic pollutants in sewage effluent and receiving seawater in the Arctic region of Kongsfjorden. (March 2020) - Choi, Younghun; Kim, Kitae; Kim, Deokwon; Moon, Hyo-bang; Jeon, Junho
Abstract: Ny-Ålesund, one of four permanent settlements on Spitsbergen in Svalbard, is a research town that includes scientific institutes from many countries. Because of daily-used chemicals (e.g., pharmaceutical and personal care products (PPCPs)) used by residents in the area, generated sewage is considered as a point source in the Kongsfjorden. The aim of the present study was to identify and quantify organic pollutants in the effluent and along the shoreline and offshore via target, suspect, and non-target screening using liquid chromatography–high-resolution mass spectrometry. We tentatively identified 30 compounds using the suspect and non-target screening methods in effluent samples from our first visit to the settlement in 2016. Among these, 3 were false positive, 24 were confirmed, and the 3 remaining compounds were not confirmed because of a lack of reference standards. Of the confirmed, 21 were quantifiable and considered target compounds for the 2nd year study. The quantified compounds in the effluent samples in 2017 totaled 17, including PPCPs, pesticides, perfluorinated compounds, and their metabolites. Some of the compounds, such as caffeine, paraxanthine/theophylline, acetaminophen, cetirizine, diethyl toluamide (DEET), and icaridin, were also detected in the receiving seawater. The concentration range was from 4 to 280, 000 ng/L in the effluent and 2–98 ng/L in the seawater. Other 24 compounds were tentatively identified in the second-year effluent samples. Five were further confirmed using reference standards. Prioritization was performed on the 47 substances screened in Ny-Ålesund using the exposure and toxicity index. As the result, the top seven substances of concern present were perfluorooctanesulfonic acid (PFOS), triphenyl phosphate (TPHP), irbesartan, DEET, acetaminophen, caffeine, and paraxanthine/theophylline. As the effluent was identified as a source of the concerned organic pollutants, an emission reduction strategy should take place for protection of Arctic Fjorden environment. Graphical abstract: Image 1 Highlights: Target, suspect, and non-target screening were applied to Ny-Ålesund effluent and receiving Fjorden in the Arctic environment. Seventeen organic substances were quantitatively analyzed whereas additional 30 were identified in the effluent. Caffeine and its metabolite were detected at high concentrations in the effluent and found even in remote seawater. Perfluoroalkyl substances, organophosphate flame retardants, and insect repellents were suggested as most concerned substances. Abstract : Ny-Ålesund effluent discharged with pharmaceuticals, perfluoroalkyl substances, organophosphate flame retardants, and insect repellents should be considered as a point source of the Kongsfjorden in the Arctic environment.